Herpesviruses enhance fibrin clot lysis - Gershom, Edwin S.; Vanden Hoek, Amanda L.; Meixner, Scott C.; Sutherland, Michael R.; Pryzdial, Edward L.G. (Thrombosis and Haemostasis, 2012)
The incorporation of virus- and host-derived procoagulant factors initiates clotting directly on the surface of herpesviruses, which is an explanation for their correlation to vascular disease. The virus exploits the resulting thrombin to enhance infection by modulating the host cell through protease activated receptor (PAR) 1 signalling. Prior reports demonstrated that at least one herpesvirus expresses surface annexin A2 (A2), a cofactor for tissue plasminogen activator (tPA)-dependent activation of plasminogen to plasmin. Since plasmin is both a fibrinolytic protease and PAR agonist, we investigated whether herpesviruses enhance fibrinolysis and the effect of plasmin on cell infection. Herpes simplex virus types 1 (HSV1) and 2, and cytomegalovirus (CMV) purified from various cell lines each accelerated the proteolytic activation of plasminogen to plasmin by tPA. Ligand blots identified A2 as one of several plasminogen binding partners associated with the virus when compared to an A2-deficient virus. This was confirmed with inhibitory A2-antibodies. However, A2 was not required for virus-enhanced plasmin generation. HSV1, HSV2 and CMV accelerated tPA-dependent fibrin clot lysis by up to 2.8-fold. Modest plasmin generation and fibrinolysis was detected independent of exogenous tPA, which was inhibited by plasminogen activator inhibitor type-1 and ε-aminocaproic acid; however, the molecular basis remains speculative. Up to a ∼6-fold enhancement of infection was provided by plasmin-mediated cell infection. Inhibitory antibodies revealed that plasmin increased HSV1 infection through a mechanism involving PAR2. Thus, virus-enhanced fibrinolysis may help explain the paradox of the highly procoagulant in vitro herpesvirus surface eliciting only relatively weak independent vascular disease risk.
Keywords: Fibrinolysis; herpes simplex virus; cytomegalovirus; tissue plasminogen activator; plasmin